LIGHTWEIGHT PSEUDORANDOM NUMBER GENERATOR MODEL FOR THE INTERNET OF THINGS - Popereshnyak , Svitlana; Raichev , Alexey (Science-based technologies, 2021)
The paper presents the types of random number generators and their disadvantages. Described is a lightweight and fast pseudo-random number generator useful for resource-constrained devices such as those used in the IoT. The article is devoted to the development of lightweight pseudo-random number generators. The principles of designing a lightweight pseudo-random number generator are described. Requirements for the quality of a lightweight pseudo-random number generator are formulated.